Implementation of Design Thinking Methods in Information Systems Academic Guidance at the Information Systems Department Faculty of Computer Science Sriwijaya University - Kelana, Nurullah Marina; Heroza, Rahmat Izwan; Juanta, Palma (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2022)
During their study period, one of the programs provided to students is academic guidance. Academic mentoring is an activity where students consult academic supervisors which aim to help students plan studies and solve study problems, one example is the academic mentoring program at the Information Systems Department, Faculty of Computer Science, Sriwijaya University. However, in practice there are problems experienced by students but they are not detected from the start because of the low monitoring of their academic supervisors which causes delays in graduation. This study aims to produce a prototype design of the Academic Guidance Information System so that it can be used as a platform for monitoring student guidance. The method used is the design thinking method which has 5 stages, namely empathize, define, ideate, prototype and test. At the ideate and prototype stages, the Fogg Behavior Model theory is used as a reference material. Evaluation of the prototype design results using the Maze Design usability tool. Testing uses two test methods, namely the Mission Usability Score (MIUS), Maze Usability Score (MAUS) and System Usability Score (SUS). The MIUS and MAUS tests got a score of 78 and entered the medium/marginal characteristics. The SUS calculation gets a score of 90.25 which leads to the acceptable category with a grade scale (A). The test results were carried out with 1 test iteration to 20 respondents and showed that the design had met the feasibility standard. Keywords : Information Systems, Academic Guidance, Design Thinking Methods, Fogg Behavior Model, Maze Design.